PENGARUH HEDONIC SHOPPING MOTIVATION DAN PRICE DISCOUNT TERHADAP IMPULSE BUYING PENGGUNA MARKETPLACE SHOPEE (Survei pada mahasiswa Program Studi D4 Manajemen Pemasaran Politeknik Negeri Malang) - Elinda Vita Sari; Masreviastuti Masreviastuti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The popularity of online shopping has increased in recent years. The emergence of Shopee, which provides attractive offers and supported by the hedonistic lifestyle of the people who are accustomed to shopping to buy things they dream of, not what they need, can trigger the phenomenon of Impulse Buying. This study aims to analyse the effect of Hedonic Shopping Motivation and Price Discounts on Impulse Buying for Shopee marketplace users. This research was explanatory research using a quantitative approach. The variables are Hedonic Shopping Motivation (X1), Price Discount (X2), and Impulse Buying (Y). The population of this research is D4 Marketing Management Students at State Polytechnic of Malang. Research data was collected by distributing online questionnaires via Google Form to 100 respondents. The sampling technique used non-probability sampling technique with purposive sampling method. The data analysis of this research used descriptive analysis, validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination test, and hypothesis testing. The results of data analysis showed that the Hedonic Shopping Motivation and Price Discount variables partially and simultaneously had a positive effect on Impulse Buying. The analysis of the coefficient of determination showed that Hedonic Shopping Motivation and Price Discounts affect Impulse Buying by 79.4% and the remaining 20.6% was influenced by other variables that not discussed in this research. Therefore, it is hoped that Shopee will always present attractive products and provide offers such as Price Discounts that can trigger hedonic motivation for Shopee marketplace users so that Impulse Buying occurs.